2022
DOI: 10.3389/femat.2022.913280
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedrite Thermoelectrics: From Fundamental Science to Facile Synthesis

Abstract: Thermoelectric materials have a long and storied history in the research and development of semiconductor materials, being the first such class of materials to be investigated. Thermoelectrics may be used to convert heat to electricity or, alternatively, to liberate or absorb heat upon electrical excitation. They thus find application in thermoelectric generators for converting heat from a primary source or a waste stream to useful electrical power, and as solid state heating and cooling devices. In spite of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…Elemental compositions for all tetrahedrite nanoparticles were within the compositional range of Cu 12−14.5 Sb 4−4.5 S 13 that is commonly observed in natural and synthetic tetrahedrite materials. 24,[39][40][41]61,62 The elemental compositions determined by EDS mapping for all ternary undoped, quaternary singledoped, and quintenary codoped tetrahedrite nanoparticles are available in Table 1. An SEM image alongside EDS maps (Figure 4d−i) taken for the Cu 11 Fe 0.5 Mn 0.5 Sb 4 S 13 codoped tetrahedrite nanomaterials indicates that constituent elements and dopants were distributed homogeneously throughout the sample, confirming that no amorphous impurities were found in the tetrahedrite nanomaterials.…”
Section: Structural and Compositional Characterizationmentioning
confidence: 99%
“…Elemental compositions for all tetrahedrite nanoparticles were within the compositional range of Cu 12−14.5 Sb 4−4.5 S 13 that is commonly observed in natural and synthetic tetrahedrite materials. 24,[39][40][41]61,62 The elemental compositions determined by EDS mapping for all ternary undoped, quaternary singledoped, and quintenary codoped tetrahedrite nanoparticles are available in Table 1. An SEM image alongside EDS maps (Figure 4d−i) taken for the Cu 11 Fe 0.5 Mn 0.5 Sb 4 S 13 codoped tetrahedrite nanomaterials indicates that constituent elements and dopants were distributed homogeneously throughout the sample, confirming that no amorphous impurities were found in the tetrahedrite nanomaterials.…”
Section: Structural and Compositional Characterizationmentioning
confidence: 99%
“…On the other hand, tetrahedrite, a naturally occurring mineral with inexpensive, less harmful, and earth-abundant constituents, offers a possible substitute for contemporary state-of-the-art thermoelectric materials. 11,12 The compound Cu 12 Sb 4 S 13 , known as tetrahedrite, is a mineral sulfide that develops with the space group I 4̄3 m above 88 K. 13 The BCC unit cell has two formula units; each formula unit contains two types of copper atoms, Cu(1) at 12 d and Cu(2) at 12 e , and two kinds of sulfur atoms, S(1) at 24 g and S(2) at 2 a Wyckoff sites respectively. The antimony atom sits at 8 c Wyckoff site.…”
Section: Introductionmentioning
confidence: 99%
“…S1: Rietveld refined patterns of the samples (a) x = 0, (b) x = 0.2, (c) x = 0.6, and (d) x = 0.8; Table S1: Rietveld refinement results for Gd and Se double substituted samples; Tables S2-S6: The Wyckoff sites and atomic coordinates (x, y, z) for all the samples; Table S7: Lattice parameters of the Cu 3 SbS 4 phase in the double substituted samples; hand, tetrahedrite, a naturally occurring mineral with inexpensive, less harmful, and earth-abundant constituents, offers a possible substitute for contemporary state-of-the-art thermoelectric materials. 11,12 The compound Cu 12 Sb 4 S 13 , known as tetrahedrite, is a mineral sulfide that develops with the space group I4 ˉ3m above 88 K. 13 The BCC unit cell has two formula units; each formula unit contains two types of copper atoms, Cu(1) at 12d and Cu(2) at 12e, and two kinds of sulfur atoms, S(1) at 24g and S(2) at 2a Wyckoff sites respectively. The antimony atom sits at 8c Wyckoff site.…”
Section: Introductionmentioning
confidence: 99%
“…Since Suekuni et al reported the thermoelectric properties of Cu 12 Sb 4 S 13 for the first time in 2012, 5,8 improve their thermoelectric performance. Wang 14 Thin-film thermoelectric materials offer numerous advantages, including low costs, low weights, and niche deployment opportunities.…”
Section: ■ Introductionmentioning
confidence: 99%